Assessment of select synthetic cannabinoid receptor agonist bias and selectivity between the type 1 and type 2 cannabinoid receptor - Ayat Zagzoog (Nature Portfolio, 2021)
Abstract The first synthetic cannabinoid receptor agonists (SCRAs) were designed as tool compounds to study the endocannabinoid system’s two predominant cannabinoid receptors, CB1R and CB2R. Unfortunately, novel SCRAs now represent the most rapidly proliferating novel psychoactive substances (NPS) of abuse globally. Unlike ∆9-tetrahydrocannabinol, the CB1R and CB2R partial agonist and the intoxicating constituent of Cannabis, many SCRAs characterized to date are full agonists of CB1R. Gaining additional insight into the pharmacological activity of these SCRAs is critical to assess and regulate NPSs as they enter the marketplace. The purpose of this study was to assess select SCRAs recently identified by Canadian police, border service agency, private companies and the illicit market as potential CB1R and CB2R agonists. To this end, fifteen SCRAs were screened for in vitro activity and in silico interactions at CB1R and CB2R. Several SCRAs were identified as being highly biased for cAMP inhibition or βarrestin2 recruitment and receptor subtype selectivity between CB1R and CB2R. The indazole ring and halogen-substituted butyl or pentyl moieties were identified as two structural features that may direct βarrestin2 bias. Two highly-biased SCRAs—JWH-018 2′-napthyl-N-(3-methylbutyl) isomer (biased toward cAMP inhibition) and 4-fluoro MDMB-BINACA (biased toward βarrestin2 recruitment) displayed unique and differential in vivo activity in mice. These data provide initial insight into the correlations between structure, signalling bias, and in vivo activity of the SCRAs.